K-State Turfgrass Research 2012 - Kansas State University. Agricultural Experiment Station; Cooperative Extension Service (Kansas Agricultural Experiment Station Research Reports, 2012)
Turfgrass Research 2012 contains results of projects conducted by K-State faculty and graduate students. Articles included in this Report of Progress present summaries of research projects that were completed recently or will be completed in the next year or two. Specifically, this year's report presents summaries of research on turf establishment and management, variety evaluations, pest management, and water issues and drought.
Keywords: Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 1071; Kansas Agricultural Experiment Station contribution; no. 12-375-S; Turfgrass; Kansas; Weed control; Disease control; Water management; Drought